Renegades born in the USA : dreams, myths, music - Obama, Barack (New York Crown, 2021)
Two longtime friends share an intimate and urgent conversation about life, music, and their enduring love of America, with all its challenges and contradictions, in this stunningly produced expansion of their groundbreaking Higher Ground podcast, featuring more than 350 photographs, exclusive bonus content, and never-before-seen archival material
Keywords: Springsteen, Bruce